Financial Literacy in Family and Economic Behavior of University Students: A Systematic Literature Review - Narmaditya, Bagus Shandy; Sahid, Sheerad (The Journal of Behavioral Science, 2023)
Technological advancement has impacted various sectors, forcing university students to face numerous challenges and opportunities. Understanding economic behavior will avoid students from debt traps and possibly enhance financial and overall well-being in students . This study aimed to conduct a systematic literature review on the relationship between financial family literacy and the economic behavior of students. To perform the systematic review, this research followed the guidelines of preferred reporting items for systematic reviews and meta-analyses (PRISMA) to reach a deeper understanding. This study formulated four research questions regarding the family financial literacy and economic behavior among university students. The results indicated that the family financial literacy can be developed through various aspects : socialization, habituation, exemplary, and discussion, while economic behavior is formed into three: consumption, entrepreneurship, and finance. The findings also confirmed that family financial literacy can drive students’ economic behavior. The results also noted that the government and educational policy supports are required to deal with changes in students’ economic behavior by implementing a particular program at the formal and informal education levels.